High Reversible Lithium Storage Capacity and Structural Changes of Fe2O3 Nanoparticles Confined inside Carbon Nanotubes - Yu, Wan-Jing; Zhang, Lili; Hou, Peng-Xiang; Li, Feng; Liu, Chang; Cheng, Hui-Ming (Advanced energy materials, 2016)
The structural evolution of electrochemically prelithiated Fe2O3 nanoparticles confined in carbon nanotubes (CNTs) during lithium insertion/extraction is studied by in situ transmission electron microscopy. It is found that the aggregation and coarsening of Fe core‐containing Li2O (Fe@Li2O) nanograins formed during the charge process are prevented by the spatial restriction of the CNTs. A high reversible capacity of 2071 mA h g−1 for the encapsulated Fe2O3 nanoparticles in CNTs is demonstrated when the material is used as the anode of lithium ion batteries. This is the highest reversible capacity ever reported for an Fe2O3 electrode. The significantly improved lithium storage capacity of the Fe2O3 nanoparticles is attributed to the extra lithium storage due to the enhanced interfacial lithium storage and reversible reaction of LiOH to form LiH and solid‐electrolyte‐interphase conversion originating from the nanoconfinement of CNTs as well as the very small particle size of the Fe@Li2O nanograins and their good electrical contact with CNTs. An in situ transmission electron microscopy study reveals that carbon nanotubes (CNTs) accommodate volume expansion of lithiated Fe2O3 nanoparticles and prevent their exfoliation and electrical disconnection, hence leading to improved lithium‐storage performance. A high lithium‐storage‐capacity is achieved for the Fe2O3 confined inside CNTs, due to the enhanced interfacial lithium reaction, reversible reaction of LiOH, and solid‐electrolyte‐interphase conversion by the CNT nanoconfinement.